The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.4049/jimmunol.178.7.4506
|View full text |Cite
|
Sign up to set email alerts
|

Collagen Distribution and Expression of Collagen-Binding α1β1 (VLA-1) and α2β1 (VLA-2) Integrins on CD4 and CD8 T Cells during Influenza Infection

Abstract: Most viral infections occur in extralymphoid tissues, yet the mechanisms that regulate lymphocytes in these environments are poorly understood. One feature common to many extralymphoid environments is an abundance of extracellular matrix. We have studied the expression of two members of the β1 integrin family of collagen-binding receptors, α1β1 and α2β1 (CD49a, VLA-1 and CD49b, VLA-2, respectively), on CD4 and CD8 T cells during the response to influenza infection in the lung. Flow cytometry showed that wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
82
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 74 publications
(86 citation statements)
references
References 51 publications
4
82
0
Order By: Relevance
“…The ␣ 1 ␤ 1 collagen-binding integrin VLA-1 is an important feature of memory CD8 T cells that allows them to be maintained in extralymphoid sites (9) and regulates the precise localization of CD4 and CD8 T cells within the collagen-rich structure of the lung (28). In this present study, we focused on the function of VLA-1 during the acute phase of the infection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The ␣ 1 ␤ 1 collagen-binding integrin VLA-1 is an important feature of memory CD8 T cells that allows them to be maintained in extralymphoid sites (9) and regulates the precise localization of CD4 and CD8 T cells within the collagen-rich structure of the lung (28). In this present study, we focused on the function of VLA-1 during the acute phase of the infection.…”
Section: Discussionmentioning
confidence: 99%
“…VLA-1 is the major receptor for type IV collagen, which is abundant in the lung and found in the basement membranes of the endothelium and epithelium (28,47). In lymphoid tissues, fibroblastic reticular cells envelop collagen fibrils, and that these collagen fibrils are located in the interfollicular zones (48,49).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD49a is also known as integrin α1 and can associate with the integrin β1 subunit (CD29) to form the CD49a/CD29 (VLA-1) heterodimer, which is responsible for retaining lymphocytes in tissues (Ray et al, 2004;Richter et al, 2007). By parabiosis studies, CD49a was also found to be a marker of trNK cells in other tissues.…”
Section: Cd49a As a Common Marker For Trnk Cellsmentioning
confidence: 89%
“…By parabiosis studies, CD49a was also found to be a marker of trNK cells in other tissues. Akin to the liver, uterus, skin and adipose contain high frequency of CD49a + DX5 − trNK cells (Richter et al, 2007;Sojka et al, 2014a). In contrast to liver and skin trNK cells, uterus NK cells are T-bet-independent and express high levels of Eomes (Sojka et al, 2014a;Tayade et al, 2005).…”
Section: Cd49a As a Common Marker For Trnk Cellsmentioning
confidence: 99%